Case Report: A Novel Compound Heterozygous Mutation of the FRMD4A Gene Identified in a Chinese Family With Global Developmental Delay, Intellectual Disability, and Ataxia - Pan, Yuhua; Guo, Xiaoling; Zhou, Xiaoqiang; Liu, Yue; Lian, Jingli; Yang, Tingting; Huang, Xiang; He, Fei; Zhang, Jian; Wu, Buling; Xiong, Fu; Yang, Xingkun (Frontiers in Pediatrics, 2021)
Background FERM domain-containing protein 4A (FRMD4A) is a scaffolding protein previously proposed to be critical in the regulation of cell polarity in neurons and implicated in human intellectual development. Case Presentation We report a case of a 3-year-old boy with corpus callosum anomaly, relative macrocephaly, ataxia, and unexplained global developmental delay. Here, compound heterozygous missense mutations in the FRMD4A gene [c.1830G>A, p.(Met610Ile) and c.2973G>C, p.(Gln991His)] were identified in the proband, and subsequent familial segregation showed that each parent had transmitted a mutation. Conclusions Our results have confirmed the associations of mutations in the FRMD4A gene with intellectual development and indicated that for patients with unexplained global developmental delay, the FRMD4A gene should be included in the analysis of whole exome sequencing data, which can contribute to the identification of more patients affected by this severe phenotypic spectrum. Keywords Global developmental delay, FRMD4A, corpus callosum anomaly, compound heterozygous missense mutations, intellectual disability